A rare case of brain hemorrhage secondary to venous angioma in the right parietal lobe: case report and literature review - Juan Manuel Altamirano; Karla Salinas-Barboza; Eduardo Lopez-Ortiz; Luis Miguel Alfonso Fernandez-Gutiérrez (Egyptian Journal of Neurosurgery)
Abstract Background Venous angiomas, also known as developmental venous anomalies (DVAs), are congenital vascular malformations that typically do not cause neurological symptoms. However, in rare cases, they can present with headaches, seizures, and even hemorrhages. This report highlights a rare case of a brain hemorrhage secondary to a venous angioma in the right parietal lobe without the common association with a cavernoma. Case presentation A 41-year-old woman experienced a sudden and severe headache, dizziness, left-sided hemihypoesthesia followed by seizures. Initial brain CT scans and MRI revealed a right parietal lobe bleed with a nodular hyperintense lesion on T1 and T2 sequences with lobulated borders and a hemosiderin halo on gradient echo sequences, initially suspected to be a cavernoma. Subsequently, the lesion was surgically resected using neuronavigation. The neuropathologic evaluation confirmed a venous angioma. Postoperatively, the patient was managed with antiepileptic medication and remained with left-sided hemihypoesthesia. Follow-up imaging showed stable residual gliosis and no active vascular anomalies. Conclusions This case underscores the importance of thorough pathological assessment and advanced imaging in accurately diagnosing DVAs. While typically benign, DVAs can present significant clinical challenges when symptomatic. This case is particularly notable for the absence of an associated cavernoma, which is more commonly seen and often responsible for hemorrhagic presentations.